2013
DOI: 10.1007/s00264-013-2133-9
|View full text |Cite
|
Sign up to set email alerts
|

Soft-tissue balancing in total knee arthroplasty: cruciate-retaining versus posterior-stabilised, and measured-resection versus gap technique

Abstract: Purpose The purpose of this study was to prove the hypothesis that soft tissues are well balanced using the gap technique with a navigation system in cruciate-retaining (CR) and posterior-stabilised (PS) total knee arthroplasty (TKA), leading to better clinical outcomes compared with the measuredresection technique. Methods One hundred and thirty-five TKAs (90 CR and 45 PS) were performed in patients with varus-type osteoarthritis using the gap technique guided by the offset-type tensor and a navigation system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 32 publications
0
43
1
Order By: Relevance
“…Rotational adjustment deviations of up to 6°are, however, not an uncommon feature when using the gap-balancing technique [20], and a symmetrical flexion gap is crucial to its success [18,19]. Comparable clinical results are reported with both techniques [21][22][23].…”
Section: Introductionmentioning
confidence: 76%
“…Rotational adjustment deviations of up to 6°are, however, not an uncommon feature when using the gap-balancing technique [20], and a symmetrical flexion gap is crucial to its success [18,19]. Comparable clinical results are reported with both techniques [21][22][23].…”
Section: Introductionmentioning
confidence: 76%
“…Numerous studies have reported on the kinematics, clinical efficacy and life‐span of CR TKA and posterior stabilized TKA. Each type of prosthesis has advantages and disadvantages. The aim of TKA is to reconstruct the mechanical axis of the knee via bone resection and/or soft tissue balance.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a total knee replacement (TKA), retaining PCL can assist in maintaining the natural knee movements and increasing the 'normal' feeling [30]. A clinical study demonstrated that retaining the PCL in TKA performed better than posterior-stabilised TKA in terms of achieving an equalized rectangular gap which contributed to ensure proper kinematics of the knee joint [31]. The result indicated that, in patients with severe OA knees who received TKA, retaining the ligament of the joint may conduce to the dynamic stability of the joint and help to improve the patient satisfaction of sensation.…”
Section: Discussionmentioning
confidence: 98%